2022
DOI: 10.32479/ijeep.13565
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Efficiency and Energy Audit to Improve Environmental Performance: An Empirical Study of Hotels in Bali-Indonesia

Abstract: This paper examines a conceptual framework that describes the relationship between energy eco-efficiency, energy audit and environmental performance. In this paper, the authors argue that eco-efficiency and energy audits can directly affect environmental performance. This paper examines responses to a survey of general managers in hotel companies registered with the Indonesian Central Bureau of Statistics. The time horizon of data collection is cross-sectional. The hypothesis was tested using a multiple linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 35 publications
3
29
1
5
Order By: Relevance
“…Based on the results of this study, it was also found that one of the massive energy conservation efforts carried out by textile companies in East Java is a kind of earth hour activity, where humans for one hour from eight thirty at night to nine thirty at night turn off all electric power except in strategic public places such as hospitals (Saputra et al, 2022). The Government of the Republic of Indonesia continues to strive to spur the development of green industries to prioritize efficiency and effectiveness in the use of resources in a sustainable manner.…”
Section: Resultsmentioning
confidence: 69%
“…Based on the results of this study, it was also found that one of the massive energy conservation efforts carried out by textile companies in East Java is a kind of earth hour activity, where humans for one hour from eight thirty at night to nine thirty at night turn off all electric power except in strategic public places such as hospitals (Saputra et al, 2022). The Government of the Republic of Indonesia continues to strive to spur the development of green industries to prioritize efficiency and effectiveness in the use of resources in a sustainable manner.…”
Section: Resultsmentioning
confidence: 69%
“…Perceptions of ease of use of IT stimulate perceptions of perceived usefulness, attitude, behavioral intention, and actual use. behavior), and further encourage the achievement of better performance (Saputra et al, 2020). Fanny (2015) and Tika (2006) in their research managed to reveal that perceived ease of use has a positive effect on auditor performance in conducting audits.…”
Section: Ease Of It / Ease Of Use and Its Ability Tomentioning
confidence: 99%
“…If performance decreases, it will gradually threaten the company and result in the company going bankrupt (Lu & Sapra, 2019). In this case, employees are always required to perform even better to effectively and efficiently achieve company goals (Saputra, Subroto, et al, 2022). Business performance measures are used for investment decisions, financing and comparisons by external parties.…”
Section: Introductionmentioning
confidence: 99%
“…Second, within a destination area, tourist villages tend to develop quantitatively but need more substantial competitiveness. Inspired by the success of one tourist village, other villages are competing to become new tourist destinations (Saputra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation